Distribution Power Grids Modeling using ETAP - Solis-Ortega, Rebeca (2025)
This paper introduces a methodology for evaluating the modeling and simulation of electrical distribution networks amidst significant integration of distributed generation. The Electrical Transient Analyzer Program (ETAP®) was utilized to model and simulate a medium voltage distribution network in Costa Rica, incorporating criteria for determining accommodation capacity based on voltage, overload, and current considerations. Our findings demonstrate the effectiveness of this approach in identifying and assessing critical points within the system, thereby eliminating the need for additional mathematical techniques. We underscore the importance of maintaining updated databases to ensure the reliability and validity of results. In conclusion, the simulation tool utilized exhibits the necessary capacity to analyze the integration of distributed generation, providing clear insights for strategic decision-making within the electricity sector.